2017
DOI: 10.1007/s11748-017-0754-4
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of variation in bronchovascular pattern of the right middle and lower lobes of the lung using three-dimensional CT angiography and bronchography

Abstract: ObjectivesGeneral thoracic surgeons must be familiar with anatomical variation in the pulmonary vessels and bronchi. Here, we analyzed the bronchovascular pattern of the right middle lobe (RML) and right lower lobe (RLL) of the lung using three-dimensional CT angiography and bronchography (3DCTAB).MethodsWe reviewed the anatomical patterns of the pulmonary vessels and bronchi in 270 patients using 3DCTAB images.ResultsThe branching patterns of vessels and bronchi of RML and S6 were classified according to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
78
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(83 citation statements)
references
References 9 publications
4
78
1
Order By: Relevance
“…Although a previous report showed various patterns of branches of PA and bronchus in the right lung using 3D-CT, no reports have revealed that only A7a branched from the right main PA [ 3 ]. Only two case reports identified lung resections with A7 branching from the right main PA [ 1 , 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a previous report showed various patterns of branches of PA and bronchus in the right lung using 3D-CT, no reports have revealed that only A7a branched from the right main PA [ 3 ]. Only two case reports identified lung resections with A7 branching from the right main PA [ 1 , 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to a previous report, the branching pattern of B7 and A7 was classified into four types: B 7 a type, B 7 ab type, B 7 b type, and BX 7 type. The B 7 a was the most common (74.8%) among the other types: B 7 ab type (14.8%), B 7 b type (4.8%), and BX 7 type (5.6%) [ 3 ]. In our case, the PA pattern and bronchus branching were compatible with the B 7 ab type, in which there are two bronchi (B7a and B7b) and two arteries (A7a and A7b).…”
Section: Discussionmentioning
confidence: 99%
“…Anatomical variation also makes it difficult to perform S7 segmentectomy. Chujo et al [5] and Nagashima et al [6] independently reported on the anatomical variations of S7. Chujo et al classified the patterns of B7 and A7 branching into 5 types, while Nagashima et al classified the B7 branching patterns into 4 types.…”
Section: Discussionmentioning
confidence: 99%
“…The anatomical patterns are diverse, and the spatial configuration of the arteries, veins, and bronchi makes the entire picture even more difficult to understand. 3D-CTAB allows a 360-degree view of lung anatomy, and leads to rapid and intuitive recognition of individual anatomical patterns (22,26,27). By recognizing the branching pattern and spatial configuration of a patient's anatomy, 3D-CTAB allows the surgeon to plan anatomical segmentectomy preoperatively by deciding which intersegmental veins should be used as landmarks, which artery/vein/bronchi should be dissected, and in what order.…”
Section: Preoperative Preparation Of Anatomical Segmentectomy By 3d-ctabmentioning
confidence: 99%